PERMAINAN KIMSPIEL UNTUK PEMBELAJARAN KOSAKATA DALAM KETERAMPILAN MENULIS BAHASA JERMAN - SARI, INTAN (LATERNE, 2017)
German is a foreign language subject that is in high school level. In learning a foreign language a person will not be able to communicate if not master the language vocabulary that he learned well. Vocabulary has an important role because it appears in every language skill. Understanding vocabulary is very important in every language study. This research was conducted to find out the learning of vocabulary in German writing skill through application of Kimspiel games. The subject of this research is the students at the 10th grade Bahasa in the SMAN 3 Lamongan. The purpose of this study was to describe the learning process of students on vocabulary learning in writing skills using the Kimspiel games. This is a descriptive qualitative research. The data collected using research instrument. The instruments that used in this research is observation form. The observation form used to asses student activity. Based on the results of the study, the results of the assessment on the observation sheet showed the percentage at the first observation is 63.6%, the percentage at the second observation is 88.6% and percentage at the third observation is 97.7%, student response to learning vocabulary is positive. This is evidenced by the dominant response from student response agreed with the application of kimspiel games for learning German language vocabulary. The application of Kimspiel games can add the vocabulary of learners in German language writing skills. Keywords: Kimspiel, Vocabulary